Prevalence of ESBL-producing Enterobacteriaceae isolated from blood cultures in Mali - Samba Adama Sangare; Almoustapha Issiaka Maiga; Ibrehima Guindo; Aminata Maiga; Namory Camara; Oumar Agaly Dicko; Souleymane Diallo; Flabou Bougoudogo; Laurence Armand-Lefevre; Antoine Andremont; Ibrahim Izetiegouma Maiga (Journal of Infection in Developing Countries)
Introduction: The increasing frequency of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae is becoming a serious public health concern. This study sought to determine ESBL frequency in Enterobacteriaceae isolated from patients’ blood cultures in two university teaching hospitals of Bamako, Mali. Methodology: During a three-month period, the presence of Enterobacteriaceae from blood cultures of patients admitted to the university teaching hospitals of Bamako was evaluated. The microbial identifications were initially performed with an API 20E gallery and VITEK2 locally in Mali, and then confirmation in France was performed with a mass spectrometry MALDI-TOF in the bacteriology laboratory of the university teaching hospital of Bichat. Antibiotic susceptibility profiles were determined by the diffusion method as recommended by the European Committee on Antimicrobial Susceptibility Testing (EUCAST). Results: The isolated species were K. pneumoniae (14/40; 35.0%), E. coli (11/40; 27.5%), and E. cloacae (9/40; 22.5%). Of the strains isolated, 21/34 (61.8%) had an ESBL phenotype, including 10/14 (71.4%) K. pneumoniae, 8/11 (72.7%) E. coli, and 3/9 (33.3%) E. cloacae. Resistances associated with ESBL strains of K. pneumoniae, E. coli, and E. cloacae were as follows: gentamicin (10/10, 100%; 6/8, 75%; 2/3, 67%, respectively), amikacin (2/10, 20%; 0/8, 0%; 0/3, 0%, respectively), ofloxacin (8/10, 80%; 7/8, 87%; 3/3, 100%, respectively), and cotrimoxazole (10/10, 100%; 6/8, 75%; 3/3, 100%, respectively). Conclusion: Almost two-thirds (61.8%) of Enterobacteriaceae isolated from our blood cultures were ESBL producers. Only susceptibilities to carbapenems and to amikacin were fully conserved within the strains.